PENGEMBANGAN KONTEN E-LEARNING IPS BERBASIS SELF REGULATED LEARNING - Isyarotullatifah Isyarotullatifah (Jurnal Visi Ilmu Pendidikan, 2019)
Problems found in SMP Negeri 1 Singaraja that is still the lack of learning media used and the results of study IPS students VIII class that many have not completed. This study aims to describe the design of e-learning development in IPS subjects, and also describe product effectiveness e-learning based on self regulated learning on IPS class VIII subjects at SMP Negeri 1 Singaraja. This research is development research and development model which used is Luther model. Data collection methods used were questionnaires and written tests. The results of the study are e-learning of IPS subjects developed valid by: (a) the result of the expert review shows the predicated product is good, (b) individualized trial, small group trials and field trials are showing e-learning predicate with good classification. The effectiveness of using SRL-based e-learning content shows a significant difference between the learners' learning outcomes before learning with the content of e-learning content based on SRL and after learning with the content of e-learning content based on SRL. The learning outcomes based on the mean posttest score were higher than the mean pretest score. The results show that SRL-based e-learning content can improve student learning outcomes.